Effects of biochar and biogas residue amendments on N2O emission, enzyme activities and functional genes related with nitrification and denitrification during rice straw composting. (August 2022) - Wang, Nanyi; Awasthi, Mukesh Kumar; Pan, Junting; Jiang, Shilin; Wan, Fachun; Lin, Xu; Yan, Binghua; Zhang, Jiachao; Zhang, Lihua; Huang, Hongli; Li, Hui
Graphical abstract: Highlights: N2 O, enzyme activities and functional genes were determined with different addition. Biochar addition rather than biogas residue decreased N2 O emission. Biochar enhanced nosZ gene abundance and accelerated the reduction of N2 O. NR, NiR, N2 OR, and AMO enzymes were stimulated by biochar or biogas residue addition. N2 O release significantly correlated with NH4 + -N, nosZ, nirK, 18S rDNA, TN and NO3 – -N. Abstract: This study was carried out to determine the response characteristics of N2 O emission, enzyme activities, and functional gene abundances involved in nitrification/denitirification process with biochar and biogas residue amendments during rice straw composting. The results revealed that N2 O release mainly occurred during the second fermentation phase. Biogas residue amendment promoted N2 O emission, while biochar addition decreased its emission by 33.6%. The nirK gene was abundant through composting process. Biogas residues increased the abundance of denitrification genes, resulting in further release of N2 O. Biochar enhanced nosZ gene abundance and accelerated the reduction of N2 O. Nitrate reductase (NR), nitrite reductase (NiR), N2 O reductase (N2 OR), and ammonia monooxygenase (AMO) activities were greatly stimulated by biochar or biogas residue rather than their combined addition. Pearson regression analysis indicated that N2 O emission negatively correlated with ammonium and positively correlated with nosZ, nirK, 18S rDNA, total nitrogen, and nitrate ( P  < 0.05).